PDGF‐D Promotes Epithelial–Mesenchymal Transition of Glioma Cells Through the NF‐κB/NOTCH1 Pathway - Yao Li; Yao Zhao; Minghao Shi; Xiaoshan Ma; Mingbo Jia; Zhongjun Shen; Xiaoyi Liu; Yunqian Li; Liyan Zhao (Cancer Medicine)
ABSTRACT Background Platelet‐derived growth factor‐D (PDGF‐D) is expressed at high levels in various tumors and is involved in epithelial–mesenchymal transition (EMT) and the malignant behavior of cancer cells. However, its role in glioma progression and the underlying molecular mechanisms remain unclear. Methods We used data from the Chinese Glioma Genome Atlas to evaluate the correlation among PDGF‐D expression, tumor grade, and phenotype of glioma. The in situ expression of PDGF‐D in clinical glioma specimens was analyzed through immunohistochemistry. Colony formation assays and transwell assays were performed for functional evaluation of glioma cell lines with PDGF‐D knockdown or overexpression. Western blotting and RT‐qPCR were conducted to explore molecular mechanisms. Results PDGF‐D was significantly upregulated in high‐grade glioma and was associated with the malignant phenotype and poor prognosis. Knocking down PDGF‐D in the LN18 glioma cell line reduced the expression of phosphorylated p65 and NOTCH1 and inhibited clonal proliferation, migration, invasion, and the EMT program. In contrast, inhibiting p65 phosphorylation in glioma cells overexpressing PDGF‐D led to the downregulation of NOTCH1 and reversed EMT. Conclusion PDGF‐D promotes the invasion and migration of glioma cells by activating the NF‐κB/NOTCH1 pathway.